Potencial evocado auditivo cortical com estímulo simples e complexo, avaliação motora e maturidade simbólica em usuários de implante coclear - Silva, Paula Botelho Da [UNIFESP] (2017)
Introduction: From the moment of conception, our organism presents a biological, organizational logic, a maturative and evolutionary calendar, also suffering from the stimulation and interaction with the environment. For the proper development of language, it is important and essential that the child develops his / her symbolic function abilities to reach the most complex levels of language. Auditory evoked potentials have been extensively studied in order to analyze the behavior of the auditory pathways before stimulation by the Cochlear Implant. Objective: To longitudinally characterize cortical auditory evoked potentials, the development of symbolic play and motor development in hearing impaired children with cochlear implants compared to their hearing peers. METHODS: Ten children of both genders, aged between two and eight years, six hearing impaired children and four audiologically normal children participated in this study. The hearing impaired children were cochlear implants users. All subjects underwent Motor Development Scale, symbolic maturity, and cortical auditory evoked potential assessments and were assessed at two times, assessment and reevaluation with a minimum of four months between evaluations. The results were analyzed statistically and compared the two evaluations in each group and between groups. Results and conclusions: There were no statistically significant differences for latency and amplitude of the different elicitor stimuli of cortical auditory evoked potential between evaluation and reevaluation for both groups. In the evaluation, the group of the hearing impaired presented greater amplitudes and latency for the eliciting stimuli of the cortical auditory evoked potential. Already in the reevaluation, the groups did not present statistical differences. The group of the hearing impaired presented a greater amplitude and latency of the cortical auditory evoked potential with speech stimulus. For the group of listeners, there was no statistical difference between the different eliciting stimuli. There was no statistical difference between evaluation and reevaluation of the symbolic maturity between groups and in each group. The group of the hearing impaired presented an improvement of the motor patterns in the reevaluation. The group of listeners presented better results in the motor evaluation when compared with the hearing impaired. The group of the hearing impaired had negative correlation in the evaluation between symbolic maturity and the latencies of cortical auditory evoked potentials. In the reevaluation there was a positive correlation between chronological age and motor age, chronological age and time of use of CI, chronological age and imitation symbolic maturity. The group of listeners did not present significant results for any variable, both in the evaluation and in the reevaluation.